Impact of diabetes mellitus on 30-day mortality among acute stroke patients in northern Tanzania - Eugénie M. Kamabu; Justin L. Paluku; William P. Howlett; Abid M. Sadiq; Eliada B. Nziku; Doreen T. Eliah; Ibrahim Ali Ibrahim Muhina; Fuad H. Said; Tumaini E. Mirai; Elifuraha W. Mkwizu; Furaha S. Lyamuya; Elichilia R. Shao; et al. (PLoS ONE, 2025)
Background Among acute stroke patients (ASPs), diabetes mellitus (DM) is associated with a higher risk of death, functional dependency, and recurrence. This study aimed to determine the impact of DM on the 30-day mortality among admitted ASPs in northern Tanzania. Materials and methods This was a hospital-based prospective cohort study performed among ASPs with and without DM who were admitted to Kilimanjaro Christian Medical Centre from November 2022 to May2023. ASPs were followed for 30 days after the onset of an acute stroke to identify the primary outcome, which was all-cause mortality. Descriptive statistics, logistic regression, and survival analysis were conducted, Results Out of 213 ASP, 82 (38.5%) had DM. The overall crude mortality rate was 46.9%. ASPs with DM had a higher mortality rate of 53.7% compared with those without DM (42.7%). A higher proportion of acute stroke patients with DM (84.1%) had a poor outcome (mRS 3-6) (p = 0.038). DM was statistically non-significant for 30-day mortality (aHR 1.56; 95% CI: 0.73–3.32; p = 0.252). However, fever (p = 0.005), severe admission Glasgow coma scale (p = 0.005), severe stroke (p = 0.008), elevated serum creatinine (p = 0.008), and an abnormal respiratory pattern (p = 0.042), were predictors of 30-day mortality, Conclusion This study demonstrated a high mortality in ASPs. Although DM did not have a significant impact on 30-day mortality, other factors, such as altered mental state, stroke severity, fever, elevated creatinine, and abnormal respiration, need to be accounted for that may have a significant impact on the mortality in ASPs. These findings highlight the significant burden of DM in stroke patients and underscore the importance of early diagnosis and treatment of ASPs, in the hopes of improving clinical practice and guidelines and reducing morbidity and mortality in Tanzania.